Extreme money : the masters of the universe and the cult of risk - Das, Satyajit (Financial Times Prentice Hall/Pearson, 2011)
The human race created money and finance: then, our inventions recreated us. In Extreme Money , best-selling author and global finance expert Satyajit Das tells how this happened and what it means. Das reveals the spectacular, dangerous money games that are generating increasingly massive bubbles of fake growth, prosperity, and wealth--while endangering the jobs, possessions, and futures of virtually everyone outside finance.